Intestinal Morphogenesis in Development, Regeneration, and Disease: The Potential Utility of Intestinal Organoids for Studying Compartmentalization of the Crypt-Villus Structure - Kwon, Ohman; Han, Tae-Su; Son, Mi-Young (Frontiers in Cell and Developmental Biology, 2020)
The morphology and structure of the intestinal epithelium are rearranged dynamically during development, tissue regeneration, and disease progression. The most important characteristic of intestinal epithelial morphogenesis is the repetitive compartmentalized structures of crypt-villus units, which are crucial for maintaining intestinal homeostasis and functions. Abnormal structures are known to be closely associated with disease development and progression. Therefore, understanding how intestinal crypt-villus structures are formed and grown is essential for elucidating the physiological and pathophysiological roles of the intestinal epithelium. However, a critical knowledge gap in understanding the compartmentalization of the crypt-villus axis remains when using animal models, due to obvious inter-species differences and difficulty in real-time monitoring. Recently, emerging technologies such as organoid culture, lineage tracing, and single cell sequencing have enabled the assessment of the intrinsic mechanisms of intestinal epithelial morphogenesis. In this review, we discuss the latest research on the regulatory factors and signaling pathways that play a central role in the formation, maintenance, and regeneration of crypt-villus structures in the intestinal epithelium. Furthermore, we discuss how these factors and pathways play a role in development, tissue regeneration, and disease. We further explore how the current technology of three-dimensional intestinal organoids has contributed to the understanding of crypt-villus compartmentalization, highlighting new findings related to the self-organizing-process-driven initiation and propagation of crypt-villus structures. We also discuss intestinal diseases featuring abnormalities of the crypt-villus structure to provide insights for the development of novel therapeutic strategies targeting intestinal morphogenesis and crypt-villus formation.